Out of my skull : the psychology of boredom - Danckert, James; Eastwood, John D. (John David), 1970- (Harvard University Press, 2020)
"Usually when we're bored, we try to distract ourselves. But soon enough, boredom returns. James Danckert and John Eastwood argue that we can learn to handle boredom more effectively by recognizing what research shows: boredom indicates unmet psychological needs. Boredom, therefore, can motivate us to change what isn't working in our lives"--